Changes in Functional Connectivity Following Treatment With Emotion Regulation Therapy - Scult, Matthew A.; Fresco, David M.; Gunning, Faith M.; Liston, Conor; Seeley, Saren H.; García, Emmanuel; Mennin, Douglas S. (Frontiers in Behavioral Neuroscience, 2019)
Emotion Regulation Therapy (ERT) is an efficacious treatment for distress disorders (i.e. depression and anxiety), predicated on a conceptual model wherein difficult to treat distress arises from intense emotionality (e.g., neuroticism, dispositional negativity) and is prolonged by negative self-referentiality (e.g., worry, rumination). Individuals with distress disorders exhibit disruptions in two corresponding brain networks including the salience network (i.e., “SN”) reflecting emotion/motivation and the default mode network (i.e., “DMN”) reflecting self-referentiality. Using resting-state functional connectivity analyses, seeded with primary regions in each of these networks, we investigated whether ERT was associated with theoretically consistent changes across nodes of these networks and whether these changes related to improvements in clinical outcomes. This study examined 21 generalized anxiety disorder (GAD) patients (with and without major depressive disorder (MDD)) drawn from a larger intervention trial (Renna et al., 2018), who completed resting state fMRI scans before and after receiving 16 sessions of ERT. We utilized seed-based connectivity analysis with seeds in the PCC, right anterior insula, and right posterior insula, to investigate whether ERT was associated with changes in connectivity of nodes of the DMN and SN networks with changes across the brain. Findings revealed statistically significant treatment linked changes in both the DMN and SN network nodes, and these changes were associated with clinical improvement corresponding to medium effect sizes. The results are discussed in light of a nuanced understanding of the role of connectivity changes in GAD and MDD, and begin to provide neural network support for the hypothesized treatment model predicated by ERT.